2021
DOI: 10.3390/insects12010072
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of New Kairomone-Based Lures for Cydia pomonella (Lepidoptera: Tortricidae) in Italy and USA

Abstract: Studies were conducted during the period 2019/2020 to evaluate the effectiveness of four lures for codling moth (Cydia pomonella L.) in pome fruits in Italy and the USA. Multi-component blends of sex pheromone ((E,E)-8,10-dodecadien-1-ol, PH), pear ester ((E,Z)-2,4-ethyl decadienoate, PE), (E)-4,8-dimethyl-1,3,7-nonatriene (DMNT), and pyranoid linalool oxide (6-ethenyl-2,2,6-trimethyloxan-3-ol, LOX) were loaded in either a halobutyl elastomer septum or a PVC matrix and always used in combination with acetic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 50 publications
5
20
0
Order By: Relevance
“…Second, the results from trial #16 where FR was placed in the known ‘pest hot‐spot’ in the orchard demonstrated the effectiveness of FR in reducing localized pest problems to a baseline level. Third, the relatively greater effectiveness of FR in the USA than in Italy is consistent with our recent report of geographical differences in the attractiveness of these multi‐component lures for codling moth (Preti et al., 2021a). While in the USA the four‐component lure PE/DMNT/LOX + AA outperformed other kairomone‐based lures for the highest capture of female moths, in Italy the multi‐component lures tested (PH/PE + AA, PE/DMNT/LOX + AA, and PH/PE/DMNT/LOX + AA) had an overall similar attractiveness for females (Preti et al., 2021a).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Second, the results from trial #16 where FR was placed in the known ‘pest hot‐spot’ in the orchard demonstrated the effectiveness of FR in reducing localized pest problems to a baseline level. Third, the relatively greater effectiveness of FR in the USA than in Italy is consistent with our recent report of geographical differences in the attractiveness of these multi‐component lures for codling moth (Preti et al., 2021a). While in the USA the four‐component lure PE/DMNT/LOX + AA outperformed other kairomone‐based lures for the highest capture of female moths, in Italy the multi‐component lures tested (PH/PE + AA, PE/DMNT/LOX + AA, and PH/PE/DMNT/LOX + AA) had an overall similar attractiveness for females (Preti et al., 2021a).…”
Section: Discussionsupporting
confidence: 89%
“…Most likely, the high rates of male removal achieved with our bisexual lures would be useful when the population density is low due to reduced male polygamy in disrupted orchards (Knight, 2007a). Unfortunately, adding PH to the multi‐component PE/DMNT/LOX + AA lure was shown to reduce female captures, and its use would not be justified (Preti et al., 2021a).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, limonene, linalool and ( E )‐β‐farnesene when combined with codlemone increased the number of males flying towards the odour source and shortened the response time of males (Schmera & Guerin, 2012). However, combinational effects of codlemone and HPVs can vary depending on whether they are loaded together or into separate lure matrices (Casado, 2007; Knight et al., 2019c; Preti et al., 2021). For instance, loading high amounts of PE with codlemone together in one septum lure reduced male codling moth's response to sex pheromone, but not when each compound was presented in a separate septum lure (Casado, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, loading high amounts of PE with codlemone together in one septum lure reduced male codling moth's response to sex pheromone, but not when each compound was presented in a separate septum lure (Casado, 2007). Similarly, adding a separate septum with codlemone to traps baited with the 4K blend composed of four separate lures increased male and did not affect female moth catches (Knight et al., 2019b), while adding codlemone into the same PVC lure together with PE, DMNT and pyrLOX significantly decreased female catch (Preti et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation